Penurunan Mutu Ikan Segar Hasil Budidaya Keramba Jaring Apung Di Teluk Ambon Pada Suhu Kamar - Leiwakabessy, Jusuf; Batmomolin, Wensislaus; Silaban, Bernita br.; Mailoa, Meigy N (Universitas Pattimura, 2024)
The research was conducted to determine the quality deterioration of several types of fish from floating net cage cultivation in Ambon Bay during a 10-hour of observation period at room temperature. Observations were made on test parameters such as pH, total volatile base (TVB), trimethylamine (TMA), and total microbes (TPC). The results of the analysis showed that over the course of 10 hours at room temperature, the process of quality deterioration in Lates calcarifer was slower compared to Gnathanodon speciosus and Oreochromis niloticus. This is evident in the fish quality parameter values. For instance, the average pH of the three types of fish during room temperature storage ranges from 6.13 to 6.65. The TVB value of G. speciosus and O. niloticus exceeded acceptable levels after 6 hours of storage, while the TVB value of Lates calcarifer remained acceptable even after 6 hours. At six hours, the TVB values exceeded 10 mg N%, indicating spoilage, while the TMA value in L. calcarifer sea bass did not exceed 10 mg N% after 10 hours of storage. The total microbial value of the three fish samples stored for 10 hours at room temperature still meets the standards for fresh fish quality.